The aesthetic politics of skin tone and hair texture amongst black women in Diepkloof, Johannesburg - Kwinika, Makhawukana Akani (University of the Witwatersrand, Johannesburg, 2023)
Beautification practices for Black women in South Africa reveal a complex interplay of cultural influences and individual affirmative choices. This research explores the societal factors that inspire Black women to beautify the surface-body, focusing on hair and skin, both locally and from an intra-racial perspective. The theories that the research borrows from are the Self- objectification theory, which explains the issues associated with bodily modifications and insecurities, and African Feminism, which examines the intersectionality of race, gender, and beauty standards, emphasizing the importance of examining the history of African women. Employing a qualitative methodology, data were collected through questionnaires and in-depth semi-structured interviews conducted in Diepkloof Zone 2, a Township situated in Soweto, Johannesburg, with a sample size of seven women. Thematic analysis was utilized for data analysis. The findings demonstrate that Black women’s beautification practices remain politicized globally, yet the Black beauty experience is multifaceted, ranging from personal to trivial. The study highlights the agency of Black women in redefining beauty standards globally and within the African continent, rather than merely adhering to Western norms. Recommendations include further exploration of Black women’s hair aesthetics to accommodate bald-headedness or short hair as a preference. Furthermore, to explore skin bleaching practices among Black women and understand the psychological implications of colourism and the yellow bone phenomenon beyond the internalization of whiteness.
A research report Submitted in fulfillment of the requirements for a Master of Arts Degree by Coursework and Research Report in Sociology, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2023
Keywords: Colourism; Black; Aesthetics; lightening/bleaching; Skin-tone; Hair; Women; Beauty; SDG-16: Peace, justice and strong institutions